Cardiac Regeneration: New Insights Into the Frontier of Ischemic Heart Failure Therapy - Riching, Andrew S.; Song, Kunhua (Frontiers in Bioengineering and Biotechnology, 2021)
Ischemic heart disease is the leading cause of morbidity and mortality in the world. While pharmacological and surgical interventions developed in the late 20th century drastically improved patient outcomes, mortality rates over the last two decades begun to plateau. Following ischemic injury, pathological remodeling leads to cardiomyocyte loss and fibrosis leading to impaired heart function. Cardiomyocyte turnover rate in the adult heart is limited, and no clinical therapies currently exist to regenerate cardiomyocytes lost following ischemic injury. In this review, we summarize the progress of therapeutic strategies including revascularization and cell-based interventions to regenerate the heart: transiently inducing cardiomyocyte proliferation and direct reprogramming of fibroblasts into cardiomyocytes. Moreover, we highlight recent mechanistic insights governing these strategies to promote heart regeneration and identify current challenges in translating these approaches to human patients.